Motivation and frustration of horses and mules: behavioral and physiological differences - Arruda, Liys A. de S. [UNESP]; Delagracia, Marcela F. [UNESP]; Maia, Caroline M.; da Luz, Marina P. F. [UNESP]; Narciso, Matheus H. P. M. [UNESP]; Baragli, Paolo; Filho, José Nicolau P. P. [UNESP] (My University, 2022)
Frustration responses of animals when environmental resources are present, but inaccessible may help to understand their motivation, i.e. the importance to access these resources. However, neither motivation nor frustration have been investigated in mules. Here, we investigated whether horses and mules are motivated to access a biologically relevant resource and whether they express frustration when their access is blocked. Eight mules and eight horses were tested for 3 days with varying difficulty degrees requiring physical effort to cross a barrier and access feed. The maximum effort was made on day 3 (blocked barrier). The animals were filmed during the tests and their stress levels were evaluated. Only mules exhibited significantly more behaviors associated with motivation when the barrier was blocked. However, this test situation caused both mules and horses to express behaviors associated with frustration, whereas only horses expressed a greater variation in the cortisol level. Thus, only mules are motivated to access feed, but both of them exhibit frustration when unable to access such resources, which has important welfare and management applications.
Keywords: effort spent; equid; frustration response; motivation respons